A study on length, position, variations in arterial supply and nature of lumen of appendix at different stages of life - George, Jessy Rose (International Journal of Research in Medical Sciences, 2016)
Background: The appendix or vermiform appendix is a blind-ended tube connected to the cecum, from which it develops embryologically. Since, the morphology of human appendix greatly varies at different age groups; the present study was undertaken to record the length, position, variations in arterial supply, nature of lumen of appendix at different stages of life. Methods: The morphology of human appendix was studied in 100 specimens of varying age groups after the ethical clearance. The length, position, variations in arterial supply, nature of lumen of appendix at different stages of life was recorded. Results: Present study showed that female appendices were slightly shorter (by around 1 cms) than male appendices of same age group. Also there was a gradual increase in the length of the appendix till the early 4th decade and then showed a gradual decrease. Single appendicular artery was observed in most of the cases whereas double appendicular arteries were observed only in few cases. The origin of the arteries showed variation in both cases. Conclusions: The lumen of the appendix of a young person often appears somewhat 3 cornered instead of circular but in adults usually rounded and in advancing years it may become obliterated by connective tissue replacing its mucous membrane as well as fitting its lumen.